Phytochemical screening of peronema canescens jack/ Ku Fareez Ku Halim ... [et al.] - Ku Halim, Ku Fareez; Jalani, Kathleen J.; Mohsin, Hannis Fadzillah; Abdul Wahab, Ibtisam (Faculty of Pharmacy, 2020)
Peronema canescens jack, locally known as sungkai, is used as medicinal plant because it contains chemical compounds such as peronemins, catechol, quinic acid, isovanillic acid and guaiacol. The study was conducted to determine the chromatographic profile of the peronema canescens leaves extract via liquid chromatography. It was found that the optimised mobile phase for thin layer chromatography (TLC) of peronema canescens leaves was hexane: ethyl acetate: isopropanol (7:3:0.3). In addition, high performance liquid chromatography (HPLC) chromatograms (λ = 210 and 254 nm) of the methanol extract, run in 0.1% formic acid and acetonitrile, provided eight acceptable peaks.